Pengawasan Pemilu Berkarakter Guna Mewujudkan Kedaulatan Rakyat dalam Rangka Pelaksanaan Demokrasi di Indonesia - I Nengah Suriata (Public Inspiration : Jurnal Administrasi Publik, 2023)
General elections are a major work of the state which is held periodically every 5 (five) years. In the elections on February 14 2024 to elect the People's Representative Council of the Republic of Indonesia (DPR RI), the Regional Representative Council of the Republic of Indonesia (DPD RI), the President and Vice President of the Republic of Indonesia, and to elect members of the Provincial Regional People's Representative Council (Provincial DPRD), Regency/City Regional People's Representative Council (Regency/City DPRD), as the implementation of people's sovereignty. To guarantee people's rights in the political field and legal certainty, the government regulates this in Law Number 7 of 2017 concerning General Elections (UU17/2017). Actions at every stage of holding elections can result in violations and criminal acts occurring in the jurisdiction of the Province of Bali, if supervision is not carried out it will result in the people's democratic party not running effectively and efficiently. This research method uses a normative legal research type method, with a statutory approach, namely Law 17/2017 as well as primary and secondary legal materials through literature studies that are appropriate to the problem. The results of this research show that election supervision has an effective character for the realization of people's sovereignty in the implementation of democracy in Indonesia and efficient and effective supervision of future elections by utilizing information technology or digitalization in applying the Industrial Revolution 4.0.